ANALISIS HUKUM EKONOMI ISLAM TERHADAP PRAKTEK IHTIKAR - Fasiha Kamal; Muhammad Ruslan Abdullah (Al-Amwal : Journal of Islamic Economic Law, 2018)
The purpose of this paper is to explain the Ihtikar law in trade and commercial activities. Islam emphasizes the implementation of moral values in all economic activities, so the ihtikar issue is very important to be studied in Islamic economic law. Islam basically gives freedom in carrying out economic activities, and Islam also regulates economic matters that cause harm. The results of the study found that the verses and hadith explained in this paper textually prohibit the existence of ihtikar. Ihtikar law is haram if the goods stockpiled are needed by the community which results in price increases. When this happens, Islam allows for intervention in economic activity by issuing some policies and rules that have an impact on normal prices.